PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS HIERARKI KONSEP PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN LAJU REAKSI - Kusagita, Deska; Azmi, Johni; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to develop the student’s activity paper on the subject of reaction rate. The type of this research was reserach and development (R & D) with the 4-D development model which include Define, Design, Develop, and Disseminate. This research was to develop phase and be continue with a definite tryout. This research was conducted in FKIP Riau University. The object of this research was the students’ activity paper based on the concept hierarchy. The data analysis technique used for this research was descriptive statistic descriptive. The descriptive analysis done by calculated the percentage of validation value. The average score of valuation to four expediency aspect of student’s activity sheet by validator’s team, such as the content properness, the language properness, course and the graphical has expediency value continued is 86.88%, 91.25%, 81.25% and 85.93%. Thus, the average score totality of student’s activity paper based on the problem solving subject of salt hydrolysis is 90% which is in valid criteria, means that the LKPD Developed is proper to be use. Whereas percentage response of student or collegian is 93% to LKPD with positive criteria.Key Words: Student Activity Sheet, Concept Hierarchy, and Reaction Rate